Mappings on weakly Lindelof and weakly regular-Lindelof spaces. - Alfawakhreh, Anwar Jabor; Kilicman, Adem (Universidad Politécnica de Valencia, 2011)
In this paper we study the effect of mappings and some decompositions of continuity on weakly Lindelof spaces and weakly regular-Lindelof spaces. We show that some mappings preserve these topological properties. We also show that the image of a weakly Lindelof space (resp. weakly regular-Lindelof space) under an almost continuous mapping is weakly Lindelof (resp. weakly regular-Lindelof). Moreover, the image of a weakly regular-Lindelof space under a precontinuous and contracontinuous mapping is Lindelof.